Issues Of Limiting Transboundary Water In Central Asia - V.A. Rafikov, N.A. Rafikova, A.R. Valieva, F.N. Kuziev, Z.A. Ganiev, B.I. Nosirov (Mathematical Statistician and Engineering Applications, 2023)
The new geopolitical situation in Central Asia has changed the status of water bodies and their waters. They now appear to be transboundary and, therefore, their economic use should be regulated according to the norms of international law. But the standards arising from it, obviously, are designed to be based on taking into account the peculiarities of the formation and distribution of water resources and, no less important, centuries-old traditions and the legal custom of water use and water consumption that has developed on the subcontinent. The current water generation and use situation in the subcontinent is uncertain for a number of reasons. Elimination of uncertainties, first of all, requires clarifying the regime of water generation in the context of global warming and streamlining the use of water resources. In connection with this issue, apparently, the problem of quotas for transboundary waters should also be discussed. This will somehow, probably, contribute to overcoming the accumulated collisions of water use and water consumption. The given data and judgments made it possible to propose a scheme for the distribution of transboundary waters for the expected "norm" of runoff in the future. However, the formation of runoff, as a rule, proceeds cyclically, and this property will obviously manifest itself in the future. It is possible that the energy factors under the conditions of global warming will be more powerful, which, apparently, will affect the runoff formation and cause a larger range of its fluctuations.